Highlights of ADB cooperation with civil society organizations 2020. (Metro Manila, Philippines Asian Development Bank, 2021)
Partnerships with CSOs help promote community participation and social inclusion throughout the project cycle of ADB financed operations. In 2020, ADB approved a new indicator for assessing civil society engagement as part of its efforts to enhance commitment to CSO engagement. The annual report looks at how ADB cooperation with CSOs during the year contributed to generating knowledge, tapping expertise, sharing good practices, and improving policy dialogues.
Keywords: Asian Development Bank -- Administration; Finance; Electronic books